Let's solve the equation \(5(2x + 2) - 7x = 3x + 6\).
First, distribute \(5\) on the left side:
\[ 5 \cdot 2x + 5 \cdot 2 - 7x = 3x + 6 \]
This simplifies to:
\[ 10x + 10 - 7x = 3x + 6 \]
Now, combine like terms on the left side:
\[ (10x - 7x) + 10 = 3x + 6 \]
This results in:
\[ 3x + 10 = 3x + 6 \]
Next, we can subtract \(3x\) from both sides:
\[ 10 = 6 \]
This statement \(10 = 6\) is false. Therefore, there are no values of \(x\) that satisfy the equation.
Thus, the conclusion is that the equation has no solution.